Optimal static var compensator placement for voltage stability improvement using particle swarm optimization technique - Ahmad Munzir Mohd Shamsul Bahrin (2023)
Electricity demand has grown rapidly every year these days. The growing demand gives the power system a pressure, but it can be solved by increasing more power and extending the line of the transmission. But, the use of this solution is opposed to some factors such as environmental and economic factors. These factors have been considered for further research into the design of power networks that can deliver maximum capacity of transmission at minimum cost. The study of this project is regarding the optimization technique called Particle Swarm Optimization (PSO). this proposed optimization technique used to solve the problem of SVC installation. For this research, the IEEE 26 Bus Reliability Test (RTS) is used to test the proposed optimization technique efficiencies.